Changes in tree sparrow "Passer montanus" populations from urban parks - Tomiałojć, Ludwik (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Studies of local Tree Sparrow "Passer montanus" populations from urban parks of Polish cities reveal changes in abundance and in nest site selection which differ from data collected from farmland. These changes are not always synchronous among neighbouring cities and parks. Several urban declines are difficult to explain, chiefly when obscured by the changes in the number of artificial nesting sites. One such case was a recorded decline Tree Sparrow and a switch to nesting in buildings observed in the Szczytnicki Park of Wrocław, after colonization by pine martens "Martes marten".
Keywords: Tree Sparrow; breeding numbers; nest sites; predators; urban area; Poland